2022
DOI: 10.1016/j.ijom.2021.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Spatial deviations of the temporomandibular joint after oncological mandibular reconstruction

Abstract: Spatial deviations of the temporomandibular joint (TMJ) after oncological mandibular reconstruction are important to the aesthetic and functional rehabilitation. The aim of this study was to clarify whether and how three dimensionally (3D) printed patient-specific surgical plates, and the preservation of the condyle or ramus, affect spatial deviations of the TMJ. A total of 33 patients who underwent mandibular reconstruction via computer-assisted surgery were included. Regarding absolute deviations, patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 27 publications
(86 reference statements)
1
21
0
Order By: Relevance
“…In the 3D-printed plate group, greater impact of temporomandibular joint (TMJ) deviations were found on the lesion side than the healthy side. Moreover, patients without preservation of both the condyle and ramus had significantly higher deviations of the condyle and joint space ( 21 ). This result was consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 3D-printed plate group, greater impact of temporomandibular joint (TMJ) deviations were found on the lesion side than the healthy side. Moreover, patients without preservation of both the condyle and ramus had significantly higher deviations of the condyle and joint space ( 21 ). This result was consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the deviations of the reconstructed mandible were assumed to be affected by the resection range, especially the posterior part of the mandible ( 24 ). The anatomical anchor of the fossa-condyle structure and the intact joint capsule stabilized the TMJ, and the masticatory muscles were mainly attached to the posterior mandible ( 21 ). Therefore, when the ramus was involved in the defect, the stability from the TMJ and the muscles greatly decreased, and reconstruction procedures became more complex at the same time, leading to increasing deviation.…”
Section: Discussionmentioning
confidence: 99%
“…By subtracting the quality of fitting the corrected mean deviation was calculated. This resulted in a value demonstrating the absolute deviation ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study by Yang and colleagues found that the use of CAS combined with a patient-speci c plate, speci cally a 3D-printed customized mandibular reconstruction plate, in non-extensive defects increases the spatial accuracy of the TMJ reconstruction, yielding better results than commercially available manually bending reconstruction plate 12 . Even though the patient-speci c plate can provide good results, surgeons may adopt different methods for bone xation processes such as miniplate and manually bending reconstruction plate.…”
Section: Introductionmentioning
confidence: 99%